1969
DOI: 10.2307/1936898
|View full text |Cite
|
Sign up to set email alerts
|

Home Ranges and Body Size of Lizards

Abstract: The relationship between home range, A (m2) and body weight, W (g) among adults of 13 species of terrestrial lizards was estimated as: A = 171.4W0.95. The slope of the logarithmic regression is steeper than that relating standard metabolic rate, M (cm3 O2/hr) at 30°C and body weight: M = 0.82W0.62. These functions are compared with similar regressions relating the home ranges and basal metabolic rates of birds and mammals to body size. Two major difficulties in the interpretation of such data are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
92
1
8

Year Published

1974
1974
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(105 citation statements)
references
References 20 publications
4
92
1
8
Order By: Relevance
“…Home range and body size are also highly correlated in reptiles (29), yet reptiles of a given body size have experienced far slower rates of evolutionary change than have pladuring lactation (27). These bonds are especially strong and centals of comparable body size.…”
Section: Discussionmentioning
confidence: 99%
“…Home range and body size are also highly correlated in reptiles (29), yet reptiles of a given body size have experienced far slower rates of evolutionary change than have pladuring lactation (27). These bonds are especially strong and centals of comparable body size.…”
Section: Discussionmentioning
confidence: 99%
“…The home range, which is the total area in which an individual of a particular species lives and wanders when active, and where it finds food, mates and shelter (Rose, 1982), varies considerably among lizard species, affected by some ecological factors (Turner et al, 1969). Some studies have shown that the size of a lizard's home range may be strongly influenced by the size of the animal (Turner et al, 1969;Christian & Waldschmidt, 1984;Van Sluys, 1997) or by its trophic level (Cristian & Waldschmidt, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that the size of a lizard's home range may be strongly influenced by the size of the animal (Turner et al, 1969;Christian & Waldschmidt, 1984;Van Sluys, 1997) or by its trophic level (Cristian & Waldschmidt, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, are there any characteristics that might increase their vulnerability to human threats? Studies of other groups such as reef-dwelling mantis shrimps (Reaka, 1980), terrestrial birds (Schoener, 1968), lizards (Turner, Jennrich & Weintraub, 1969) and mammals (Harestad & Bunnell, 1979) have noted positive correlations between body size and range size. It is also widely acknowledged that in macroscopic marine animals there is a strong correlation between small body size, short planktonic stage and short dispersal periods resulting in restricted geographical distributions (Hansen, 1978;Reaka, 1980;Reaka & Manning, 1981;Strathmann & Strathmann, 1982;Jablonski & Lutz, 1983;Jablonski, 1986).…”
Section: Characteristics Of Restricted-range Speciesmentioning
confidence: 99%